"Top Ten" List: A Brief Report of Adult Poisoning and Prevention Tips. (May 2016) - Dodd-Butera, Teresa; Smith-Stoner, Marilyn
Abstract : This article reviews the 10 major categories of poisoning exposures, as reported to the American Association of Poison Control Centers through the national surveillance system, provides an overview of adult poisonings, and offers tips for home care clinicians to educate themselves and patients on poison exposure, prevention, and response. Home healthcare clinicians provide a critical link in the chain of home safety throughout the care continuum. The phone number for the local poison control center should be readily available in patients' homes and known to all home healthcare staff members. The top 10 categories should be reviewed during orientation of new home care staff members and at staff meetings.